New findings of Neonothopanus (Marasmiaceae, Basidiomycota) from Ghana - Hu, Jia-Jun; Li, Yu; Li, Xiao; Frederick, Sossah Leo; Zhang, Bo (Phytotaxa, 2021)
Specimens of Neonothopanus were collected from Ghana and examined morphologically, and molecularly using the nuclear internal transcribed spacer (nrITS) and nuclear large subunit ribosomal (nrLSU) regions. Three species were recognized viz., Neonothopanus cystidiosus, a new species, Neonothopanus cystidiosus, a new record for Ghana, and Neonothopanus hygrophanus, a species already known from Ghana. Neonothopanus cystidiosus is characterized by brown spots visible on the surface of pileus when mature and the presence of clavate to cylindrical pleurocystidia. Phylogenetic trees constructed using Bayesian Inference and Maximum Likelihood analyses confirmed the results of the morphological study. Descriptions of all three species are presented with molecular work, along with a key to the known species of Neonothopanus. The addition of a new species provides a new perspective on the heterogeneity of Neonothopanus and contributes to increasing knowledge of the fungal diversity of Ghana.